Internal friction measurements in Nb-0.3wt.%Ti containing oxygen - Grandini, Carlos Roberto [UNESP]; Ferreira, LEC; Sandim, HRZ; Florencio, O.; Tejima, H.; Jordao, JAR (Editions Physique, 1996)
Internal friction measurements were made in the Nb-Ti alloy containing 0.3 wt. % of Ti, doped with various quantities of oxygen (0.04 to 0.08 wt. %) utilizing a torsion pendulum. These measurements were performed in the temperature range of 300 K to 700 K with the oscillation frequency about 1.0 Hz. The experimental results showed relaxation peaks due the stress induced ordering of oxygen atom and pairs of oxygen atom around the niobium atoms (metallic matrix) and around titanium atoms (substitutional solute).